2020
DOI: 10.3389/fendo.2020.583565
|View full text |Cite
|
Sign up to set email alerts
|

Use of Rituximab After Orbital Decompression Surgery in Two Grave’s Ophthalmopathy Patients Progressing to Optic Neuropathy

Abstract: Background: While orbital decompression can alleviate optic nerve compression and prevent further vision loss in dysthyroid optic neuropathy (DON), it cannot relieve inflammatory symptoms. Very high doses of intravenous glucocorticoids (GCs) are the first-line therapy for DON; however, the effective rate is only 40% and might be much lower in patients who fail high-dose GC pulse therapy and progressed to DON. The results of two case series studies indicated that rituximab treatment had a much better curative e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…1 shows that 76 articles of the 954 screened records were included in the review. 25–101 The literature on the use of Mabs for treating GO has been centered on blockage of IL-6 (Tocilizumab), 34,39,41,49,50,53,56,58–60,63,64,68–72,79,80,84,87,90,96–98 anti-CD20 lymphocytes (Rituximab), 26–33,35,37,38,40,42–48,51,54,55,61,62,65,67,73,89 and IGF1R (Teprotumumab). 52,66,74–78,82,85,86,88,91,92,94,95,99–101 Three articles have described Mabs that block TNF-α, 25,36,83 and one article has described Mabs that block the B-lymphocyte stimulator (BLyS) protein (Belimumab).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 shows that 76 articles of the 954 screened records were included in the review. 25–101 The literature on the use of Mabs for treating GO has been centered on blockage of IL-6 (Tocilizumab), 34,39,41,49,50,53,56,58–60,63,64,68–72,79,80,84,87,90,96–98 anti-CD20 lymphocytes (Rituximab), 26–33,35,37,38,40,42–48,51,54,55,61,62,65,67,73,89 and IGF1R (Teprotumumab). 52,66,74–78,82,85,86,88,91,92,94,95,99–101 Three articles have described Mabs that block TNF-α, 25,36,83 and one article has described Mabs that block the B-lymphocyte stimulator (BLyS) protein (Belimumab).…”
Section: Resultsmentioning
confidence: 99%
“…34,39,41,49,58,59,63,68,69,71,72,79,80,84 The same trend is true for Rituximab (64.3% articles from Europe). 26,27,30,33,35,37,[42][43][44][46][47][48]54,55,61,62,65,67,73,89 In contrast, Teprotumab has only been tested in the USA. [74][75][76][77][78]82,85,86,88,91,92,94,95,99,100,102 Most articles on the three most tested Mabs consist of case reports and case series (Tables 2-4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, DON developed in 2 of 13 patients who underwent rituximab treatment, 56 which may be caused by an excess release of cytokines by this drug. 48 Although previous review and case reports showed favorable results of rituximab treatment for DON, 54,57,58 EUGOGO guidelines recommend avoidance of its use in patients with a risk of developing DON. 1 Teprotumumab is a human monoclonal antibody inhibitor of insulingrowth factor-1 receptor.…”
Section: Other Medical Agentsmentioning
confidence: 99%